17.1: Invited Paper: Polymer‐Stabilized Blue Phase Liquid Crystal Displays Applying Novel Groove Cell Structure. Issue 1 (1st July 2013) - Tsai, Cheng‐Yeh; Tseng, Te‐Jen; Wang, Lin‐Yung; Yu, Fang‐Cheng; Lan, Yi‐Fen; Huang, Pu‐Jung; Lin, Szu‐Yu; Chen, Kuan‐Ming; Tseng, Bo‐Shiang; Kuo, Chia‐Wei; Lin, Ching‐Huan; Lu, Jen‐Kuei; et al.
Abstract Blue phase liquid crystal displays (BPLCDs) have attracted considerable attention in recent years because of its many advantages. However, BPLCDs exhibit narrow temperature range, high driving voltage, and tough process. In our works, polymer‐stabilized technology using newly optimized BPLC material was applied to enlarge BP temperature range. In order to overcome high driving voltage, 2D1G design was used to apply conventional source driver IC for cost. Furthermore, novel groove cell structure which could gain more effective electric field without adding special masks for the groove was successfully implemented. Finally, 10‐inch BPLCDs was demonstrated by optimization of ODF process.